Maternal Mortality : Report June, 1932 (London : The Maternal Mortality Committee)
1932-06 1932 1930s 20 pages MATERNAL MORTALITY REPORT JUNE, 1932 [Picture] Printed by the LONDON CALEDONIAN PRESS LTD., 74 Swinton Street, Gray's Inn Road, W.C.1, and Published by THE MATERNAL MORTALITY COMMITTEE, 13 Chester Terrace, S.W.1 292/824/1/58